An Information Operational Model for Procurement Management in the Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2023)
Research aimed to design and to assess an information operational model for procurement management in Thai supply chain. A samples are ten experts in the field of information. and supply chain. The data is analysed by means and standardized deviations. The research about an information operational model for procurement management in Thai supply chain consists of six elements namely main elements Suppliers , Producer, Finished goods and Customers. The assessment about an information operational model for procurement management in Thai supply chain using Black-Box technique. The research findings revealed that an information operational model for procurement management in Thai supply chain is appropriate at the high level which mean that This model can be develop information system.